# math (trig)

posted by .

Prove:
sin^2(x/2) = csc^2x - cot^2x / 2csc^2(x) + 2csc(x)cot(x)

On the right, factor the numberator as a difference of two perfect squares. In the denominator, factor out 2cscx.

You ought to prodeed rather quickly to the proof.

## Similar Questions

1. ### Calculus

Hello, I'm having trouble with this exercise. Can you help me?
2. ### Trigonometry

Hello all, In our math class, we are practicing the trigonometric identities (i.e., sin^2(x)+cos^2(x)=1 or cot(x)=cos(x)/sin(x). Now, we are working on proofs that two sides of an equation are equal (for example, sin(x)*csc(x)=1; sin(x)csc(x)=sin(x)/sin(x)=1; …
3. ### trig

Prove the identity sin squared 0 with line/2 = csc zero with line -cot zero with a line /2csc zero with a line
4. ### trig

verify : [sec(x) / csc(x) - cot(x)] - [sec(x) / csc(x) + cot(x)] = 2csc(x)
5. ### trig

For each expression in column I, choose the expression from column II to complete an identity: Column I Column II 1. -tanxcosx A. sin^2x/cos^2x 2. sec^2x-1 B. 1/sec^2x 3. sec x/cscx C. sin(-x) 4. 1+sin^2x D.csc^2x-cot^2x+sin^2x 5. …
6. ### Math

What is the first step. Explain please. Which expression is equivalent to cos^2x + cot^2x + sin2^x?
7. ### Trig verifying identities

I am having trouble with this problem. sec^2(pi/2-x)-1= cot ^2x I got : By cofunction identity sec(90 degrees - x) = csc x secx csc-1 = cot^2x Then split sec x and csc-1 into two fractions and multiplied both numerator and denominators …
8. ### Trigonometry

prove the ff: a.) sin(x/2) - cos(x/2) = +-sqrt(1 - sin(x)) b.) tan(x/2) + cot(x/2) = 2csc(x)
9. ### TRIGO

prove the ff: a.) sin(x/2) - cos(x/2) = +-sqrt(1 - sin(x)) b.) tan(x/2) + cot(x/2) = 2csc(x) HELP PLEASE!!
10. ### Math

Find an equation for the tangent line to the curve at (π/2 , 2). y = 4 + cot(x) - 2csc(x) I am confused how to take the derivative of this problem. When I tried to solve it I ended up with -csc^2 (x) + (2csc(x) * cot(x)). From …

More Similar Questions